2022
DOI: 10.21203/rs.3.rs-1417151/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The diabetes mellitus multimorbidity network in people over 50 years: An analysis of Chinese data

Abstract: Objective: To characterize the patients in the diabetes mellitus (DM) multimorbidity network in people over 50 years and explore the association between DM and other chronic non-communicable diseases (NCDs) and the variations in age and sex subgroups.Methods: Data on 75 NCDs were extracted from electronic medical record of 309,843 hospitalized patients older than 50-years-old who had at least one NCD. The association rules analysis was used as a novel cluster method. Result: The four NCDs that co-occurred with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Zhang used decision tree CHAID model and logistic regression model to analyze the influencing elements of patients' life quality who have type 2 diabetes [7], to understand the current situation of the quality of life of patients with type 2 diabetes, and then drew the conclusion that type 2 diabetes The quality of life of diabetic patients needs to be improved, and the disease has a greater impact on the psychological function of patients. Chen discussed the relationship between diabetes epidemiological investigation and cancer risk, using logistic regression to analysis the relationship between diabetes and tumors [8]. They found that diabetes is a risk factor for the occurrence of malignant tumors and age, gender and so on are risk factors for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang used decision tree CHAID model and logistic regression model to analyze the influencing elements of patients' life quality who have type 2 diabetes [7], to understand the current situation of the quality of life of patients with type 2 diabetes, and then drew the conclusion that type 2 diabetes The quality of life of diabetic patients needs to be improved, and the disease has a greater impact on the psychological function of patients. Chen discussed the relationship between diabetes epidemiological investigation and cancer risk, using logistic regression to analysis the relationship between diabetes and tumors [8]. They found that diabetes is a risk factor for the occurrence of malignant tumors and age, gender and so on are risk factors for diabetes.…”
Section: Introductionmentioning
confidence: 99%